The influence of swing leg technique on maximum running speed - Rottier, T. D.; Allen, S. J. (Journal of Biomechanics, 2021)
The motion of the swing leg of elite sprinters at maximum speed is markedly different from that of slower sprinters, but the mechanisms by which this difference influences performance are unknown. The aim of this study was to establish whether and, if so, how the motion of the swing leg influences maximum achievable running speed using computer simulation. A seven-segment planar computer model was constructed to simulate the stance phase of sprinting. Optimisation was used to maximise the running speed of the model using two different swing leg techniques, one representative of an elite sprint athlete, and the other of a sub-elite athlete. The maximum speed of the model increased when using the swing leg technique of the elite athlete compared with the technique of the sub-elite athlete (10.2 m s-1 vs 9.3 m s-1). This improvement in performance was due to greater horizontal displacement of the mass centre during stance (0.861 m vs 0.814 m), and an increase in average vertical ground force of 51 N (0.06 bodyweights). The increase in vertical force was due to a larger impact peak caused by more negative vertical momentum of the stance leg at touchdown, and subsequently greater torques in the joints of the stance leg which were placed in faster eccentric conditions and at angles closer to optimum during the first half of stance. It is likely that force increases in early stance associated with swing leg technique contribute to the asymmetrical vertical ground reaction force traces observed in elite sprinters.